Multiple fish species identified from China's roasted Xue Yu fillet products using DNA and mini-DNA barcoding: Implications on human health and marine sustainability. (June 2018) - Xiong, Xiong; Yao, Lili; Ying, Xiaoguo; Lu, Lixia; Guardone, Lisa; Armani, Andrea; Guidi, Alessandra; Xiong, Xiaohui
Abstract: Roasted Xue Yu fillet is among the most common fish products in China and the market appealing can be reflected by its high price that occasionally exceeds 300 RMB/kg in local supermarket. However, due to the lack of harmonization around the definition of Xue Yu, as well as the disability of visual inspection for transformed fish products, China's roasted Xue Yu fillet products are quite deep in the scandal of species adulteration. The objective of this study is to apply DNA and mini-DNA barcoding for the species identification of 153 roasted Xue Yu fillet products, on behalf of 30 brands, collected from 16 cities of China. The mislabeling rate was assessed according to three increasingly stringent definitions: 1) Xue Yu meaning Gadiformes species; 2) Xue Yu meaning Gadidae species; 3) Xue Yu meaning Gadus spp. Results highlighted a very high mislabeling rate, which reached 58% even with the least stringent definition. Only 42% of the samples were identified as belonging to Gadiformes, while the others were Scorpaeniformes, Tetraodontiformes and Lophiiformes. Moreover, the implications on human health and marine sustainability were also discussed, given the identification of poisonous Lagocephalus spp. from 37 samples and the China's rising consumption of marine resources. Highlights: Roasted fish fillet products sold as Xue Yu in China were collected. DNA and mini-DNA barcoding revealed an alarming misrepresentation rate of 58%. Implications on human health and marine conservation have been discussed.